Potentialities of pond fish farming in Kaliakair upazila under Gazipur district, Bangladesh - Rahman, Md Mahbubur; Mondal, Md Nurunnabi; Shahin, Jannatun; Fatema, Jannatul; Fatema, Mst Kaniz (Research in Agriculture Livestock and Fisheries, 2015)
Potentials and prospects of pond fish farming in improving aquaculture system in Kaliakair upazila under Gazipur district, Bangladesh were investigated. Data were collected from 60 selected fish farmers through questionnaire survey and Focus Group Discussion (FGD) during June to November, 2014. The research revealed that a highest number of pond fish farmers (61.67%) were out of training facilities and a good portion (23.33%) had no education. Pond water was found turbid seasonally (71.66%) and farmers did not exchange water during culture periods (66.67%). As a result water quality deteriorates day by day and depletion of oxygen occurs during pond farming. The average stocking density of fish was higher in the study area and the highest was found in monoculture of Climbing perch (Anabas testudineus ) (1200 individual/decimal) and lowest in carp polyculture system (195 individual/decimal). Fish production was higher in Pangus monoculture system (17.89 MT/ha/yr) and lower in Climbing perch monoculture system (10.78 MT/ha/yr), but profit was higher in Climbing perch monoculture produced 1318100 Tk./ha/yr and lower in Tilapia monoculture 397886 Tk./ha/yr. Benefit Cost Ratio was higher in Climbing perch (2.32) and lower in Pangus culture (1.34). The problems faced by the fish farmers were broadly categorized as financial, natural, technical and social. Therefore, necessary training facilities with institutional and organizational supports, credit facilities, extension services and awareness development are essential to improve aquaculture system as well as the fishers livelihoods in Kaliakair upazila of Gazipur district. Res. Agric., Livest. Fish.2(3): 517-528, December 2015